(untitled) (Damascus University Journal for legal sciences, 2025)
The Holy Qur’an paid great interest to the issue of human creation. It contained many verses that talk about the origin of man and how the creation of humans began. The emergence of some new scientific theories, especially the evolution theory, and the looking of some interpreters at it, led to the emergence of new sayings in the interpretation of those verses. The research aims to conduct a critical study of the sayings that were said in the interpretation of the verses that talk about the origin of man in the modern era. The various interpretations of the verses were collected, and the scientific and linguistic pieces of evidence for each of them were determined. Then, evaluation of those sayings and their pieces of evidence were carried out to distinguish the acceptable or refused ones in light of both the rules of interpretation and the results of experimental scientific research. It has been possible to conclude that the most correct interpretation for the origin of mankind as indicated by the Qur’anic verses is that the beginning was with the creation of Adam in an honorable manner, then Eve was created from Adam and of his same kind. The creation of Adam and his imagery were honoring for him and all his offspring. Moreover, his creation and imagery were real creation and real imagery of his offspring, not mere metaphors. Since then, this offspring began to procreate until this day and will continue until the Hour of Judgment.